INVESTIGATING CAREER INTENTION AMONG HOSPITALITY INTERNS: THE INFLUENCE OF CAREER BARRIERS - Abdul Majid, Mohd Aliff; Zulkifly, Muhammad Izzat; Fauzi, Firdaus Ahmad; Abd Majid, Hairulnizwan; Hafizuddin, Syed Putera (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This research investigates career barriers and career intentions among hospitality interns. The growing hotel and tourism industry has led to increased employment opportunities and expanded hospitality and tourism courses. Despite internships aiming to enhance, personal and social barriers hinder career intentions. The study employs a quantitative, cross-sectional approach with 111 hospitality interns. Data from an online survey was analyzed to explore relationships between career barriers and career intention. The research has been able to identify the best predictor on career intention among hospitality interns. By examining the variables, this study aims to provide insights for academic and practical improvements in career preparation for emerging hospitality professionals.